Patient Perspectives on the Prevalence and Burden of Intertriginous Psoriasis: Results from a National Survey of Adults with Psoriasis in the United States - Teri Greiling; Melodie Young; Melissa S. Seal; Robert C. Higham; April Armstrong (Adis, Springer Healthcare, 2024)
Abstract Introduction A survey was conducted by The Harris Poll on behalf of Arcutis Biotherapeutics in the USA to understand perspectives and burden of patients with psoriasis using prescription topical treatments for their disease. This manuscript presents results from the subset of patients with intertriginous psoriasis. Methods The survey was conducted online October 21-November 24, 2021, among 507 US adults aged 18+ years with psoriasis diagnosed by a healthcare provider and currently using prescription topical treatment. Participants with intertriginous psoriasis were patients with plaque psoriasis reporting symptoms in the armpit, groin, under breast, stomach fold, or between the buttocks. Results Of the 507 respondents, 320 (64%) reported symptoms in intertriginous areas at some point, typically between the buttocks (31%). Most patients with intertriginous psoriasis reported it made them feel embarrassed (80%), anxious (79%), or depressed (69%). In addition, 45% of these patients reported intertriginous psoriasis caused a negative impact on sexual anxiety or distress. Quality of life impact was reported as "very strong negative impact" in 16% of patients with groin involvement vs. 6% in patients with no groin involvement and 15% in women vs. 6% in men. Patients with intertriginous psoriasis reported that itch (61%), scaling (53%), redness (49%), and skin cracking (46%) related to intertriginous psoriasis had the greatest negative impact on quality of life. Most (86%) of these patients said they would be more adherent if a single treatment option could be used to treat all affected areas of their body. Conclusion Psoriasis involvement in intertriginous areas over the course of disease is common and has a negative impact on these patients' quality of life, particularly emotional well-being and sexual health.